Kajian Laju Infiltrasi pada DAS Air Dingin Kota Padang Ditinjau dari Perbedaan Litologi Batuan, Kemiringan Lahan, Jenis Tutupan Lahan, dan Sifat Fisik Tanah - Rendra Aulia Pratama; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2018)
Abstract. The new land clearing for residential area will be cause a reduction in open area as a place for infiltration of rainwater into the soil. The functional shift of the land can increase run off and give rise flooding. It is necessary to do a study about infiltration rate, mapping of infiltration zone, and calculation of water discharge that can be infiltrate by soil has be done at DAS Air Dingin Padang City. This research was carried out on 16 measurement points that spread at middle and downstream area of DAS Air Dingin. The data obtained is infiltration rate data, lithology description, slope of the land, type of land cover, and physical properties of soil data. Based on the result of data processing used kostiakov method, then the average of infiltration rate at research area is 0.10852 cm/s, this value is include of very low infiltration area (0.1-0.2 cm/s). The mapping of infiltration zone has divide research area into 6 zone that is the low zone infiltration 0.000599482-0.019298148 cm/s and the highest zone infiltration 0.224955543-0.569651067 cm/s. At the other, water discharge can be infiltrate by soil at research area is very low (65.402,5331 m3/hour/km2) with an area of infiltration is 20,844km2.Keywords: Infiltration Rate, Kostiakov Method, Lithology, Physical Properties of Soil, Infiltration Zone